EFFECTIVENESS OF MANAGEMENT AT THE UNIVERSITY IN CHINA - KMECOVA, Iveta (Trends in education, 2016)
This paper presents partial results of a survey aimed at identifying the views of teachers on the quality of teaching. The aim was to determine the attitude and opinion of teachers on motivational techniques, teaching methods, competence of teachers and the use of innovative elements in the learning process. The study was conducted on NCUT in Beijing, China.
Keywords: efficiency; management; teacher competence; teaching methods and means; motivational techniques; innovative means; educational process